On the Application of Information Technology of Vietnamese Firms - Anh, Tu Thuy; Mai, Vu Thi Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 2, 2018)
The fourth industrial revolution will strongly impact production, shifting the world economy to “smart” knowledge economy. Scientific and technological advances are applied to optimize production process, distribution, exchange, consumption, management, and administration. It is a real challenge for developing countries of which Vietnam is not an exception. This paper seeks to describe the current situation of the usage of information technology (IT) of Vietnamese enterprises from 2001 to 2011 as IT and information and communication technology (ICT) are core factors under the 4 th IR. From this analysis, a policy discussion is withdrawn.